Improving the TADF in Corannulene‐Based Emitters via Tuning the Strength of Donor and Acceptor Groups. Issue 4 (15th February 2023) - Jacob, Jesni M.; Jennifer G, Abigail; Varathan, Elumalai; Ravva, Mahesh Kumar
Abstract: In this investigation, a systematic study on the design and development of corannulene‐based thermally activated delayed fluorescence (TADF) emitters using density functional theory methods is carried out. Benzene, benzopyrazine, difluoro‐benzopyrazine, benzene‐1, 2‐dithiol, and tetrasulfone are introduced on corannulene bowl as electron‐withdrawing groups to alter the electron‐accepting property of corannulene. Three different donors, viz., carbazole, phenoxazine, and 5, 10‐dihydrophenazine are substituted on the rim position of corannulene to alter the absorption properties. The relationship between chemical structure and TADF property is established by evaluating the dihedral angle between donor and acceptor units, spin–orbit coupling (SOC) values, the energy difference between singlet‐triplet excited states (Δ E ST ), and rates of reverse intersystem crossing ( k RISC ). The newly designed TADF emitters show absorption in the blue to near‐IR regions depending on the strength of the donor and acceptor moieties. Careful analysis of these properties delineates the relationship between SOC values and the nature of the excited states, which is crucial for achieving high k RISC . Abstract : The newly designed thermally activated delayed fluorescence (TADF) emitters show absorption in the blue to near‐IR regions depending on the strength of the donor and acceptor moieties. The nature of excited states and the dihedral angle between donor and corannulene significantly influence spin‐orbit coupling matrix elements (SOCME) and k RISC . The importance of considering the rigidity of the TADF emitters is further emphasized here.